Linking transdisciplinary research characteristics and quality to effectiveness: A comparative analysis of five research-for-development projects - Belcher, B.; Claus, R.; Davel, R.; Ramírez, L.F. (Elsevier, 2019)
More and more effective research is needed to help address complex sustainability problems. Many research approaches have adopted more transdisciplinary characteristics as a way to improve effectiveness. However, empirical evidence of the extent to which and how transdisciplinary research design and implementation contribute to (more) effective scientific and social outcomes remains limited. This paper reports a comparative analysis of five research-for-development projects implemented in Peru and Indonesia to: characterize the extent to which projects employed transdisciplinary principles; assess the extent to which and how intended project outcomes were achieved; analyze the relationship between transdisciplinary research approaches and outcomes; and provide lessons from the experience of using a theory-based approach to evaluate a set of case studies. Our analysis demonstrates that the projects employing more transdisciplinary principles in their design and implementation make more diverse contributions and have a greater breadth of influence.